A time to tell: narrative strategies in Ecclesiastes - Christianson, Eric S. (Journal for the study of the Old Testament / Supplement series, 1998)
Christianson uses a variety of methods from art criticism to Todorov''s actantial model to sketch a compr ehensive picture of some hitherto neglected narrative elemen ts in Qoheleth''s text.